Microarray analysis of transposition targets in Escherichia coli: The impact of transcription - Manna, Dipankar (National Academy of Sciences, 2004)
Transposable elements have influenced the genetic and physical composition of all modern organisms. Defining how different transposons select target sites is critical for understanding the biochemical mechanism of this type of recombination and the impact of mobile genes on chromosome structure and function. Phage Mu replicates in Gram-negative bacteria using an extremely efficient transposition reaction. Replicated copies are excised from the chromosome and packaged into virus particles. Each viral genome plus several hundred base pairs of host DNA covalently attached to the prophage right end is packed into a virion. To study Mu transposition preferences, we used DNA microarray technology to measure the abundance of >4,000 Escherichia coli genes in purified Mu phage DNA. Insertion hot- and cold-spot genes were found throughout the genome, reflecting >1,000-fold variation in utilization frequency. A moderate preference was observed for genes near the origin compared to terminus of replication. Large biases were found at hot and cold spots, which often include several consecutive genes. Efficient transcription of genes had a strong negative influence on transposition. Our results indicate that local chromosome structure is more important than DNA sequence in determining Mu target-site selection.